DER dan PER ANALISIS PENGARUH DER (DEBT TO EQUITY RATIO) DAN PER (PRICE TO EARNING RATIO) TERHADAP MINAT CALON INVESTOR SAHAM - Setyawati, Risa; Supriono, Supriono (Jurnal Ekonomi dan Teknik Informatika (JNETI), 2023)
The background of this research is the emergence of various illegal stock trading application and the increasing number of investors in Indonesia during the Covid-19 pandemic. Economic conditions are dramatically weakened and suddenly, encouraging some societies to take quick way by making stock investments or trading without a sufficient understanding of investing. The purpose of this research is to analize the influence of Debt to Equity Ratio and Price to Earning Ratio toward the interest of stock investors. This research employs quantitative methods, secondary data sources obtained through official website of PT ABM Investama and primary data are obtained through questionnaires. Respondents in this research as many as 65 with desctiptive data analysis techniques and ststistical test. A descriptive analysis is used to test the data by using the fundamental ratio analysis method over seven fundamental ratios. Statistical tests are used to test the hypothesis and significance of the correlation between variables. The research shows that: (1) PT ABM Investama fundamental ratio analysis indicates normal and tend to be good. (2) The average stock investors interest in PT ABM Investama shares over the period 2018-2021 is by 44,63%. (3) DER and PER has a negatife and significant impact on investment interest. (4) there is a factor beyond the analysis of the fundamental ratio that affects the decisions of prospective investors.